2006
DOI: 10.1161/01.str.0000239666.46828.d7
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cognitive Transitions, Rates of Cognitive Change, and Predictors of Incident Dementia in a Population-Based First-Ever Stroke Cohort

Abstract: Background and Purpose-There are few data on long-term cognitive outcomes after first-ever stroke. We aimed to study long-term cognitive transitions, rates of cognitive change, and factors associated with incident dementia and cognitive impairment-no dementia (CIND) 2 years after first-ever stroke. Methods-A population-based cohort of incident first-ever stroke cases (nϭ99; mean age, 69.9 years) and an age-and sex-matched comparison group (nonstrokes, nϭ99) were followed up for 2 years by 3 serial examinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
2
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 16 publications
6
74
2
4
Order By: Relevance
“…32 Whether ischemic infarcts only accelerate a pre-existing cognitive impairment or whether infarcts pose a risk for developing cognitive decline also in cognitively normal subjects remains unclear. Although 2 population-based cohort studies seem to support the view that prestroke cognitive status is an independent risk factor for poststroke dementia, 28,33 other studies found no such association 34 or only for nonamnestic mild cognitive impairment but not for amnestic mild cognitive impairment, 35 which usually is considered a prodromal state of AD. A recent longitudinal cohort study re-examining this question 36 indicates that although higher levels of prestroke executive function are associated with lower risk for poststroke dementia (relative risk, 0.24; 95% confidence interval, 0.13-0.45), stroke was a disproportionate risk factor (relative risk, 4.4; 95% confidence interval, 1.35-14.63) for dementia in patients with high cognitive function.…”
Section: Evidence From Clinical and Epidemiological Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…32 Whether ischemic infarcts only accelerate a pre-existing cognitive impairment or whether infarcts pose a risk for developing cognitive decline also in cognitively normal subjects remains unclear. Although 2 population-based cohort studies seem to support the view that prestroke cognitive status is an independent risk factor for poststroke dementia, 28,33 other studies found no such association 34 or only for nonamnestic mild cognitive impairment but not for amnestic mild cognitive impairment, 35 which usually is considered a prodromal state of AD. A recent longitudinal cohort study re-examining this question 36 indicates that although higher levels of prestroke executive function are associated with lower risk for poststroke dementia (relative risk, 0.24; 95% confidence interval, 0.13-0.45), stroke was a disproportionate risk factor (relative risk, 4.4; 95% confidence interval, 1.35-14.63) for dementia in patients with high cognitive function.…”
Section: Evidence From Clinical and Epidemiological Studiesmentioning
confidence: 94%
“…7 (2) The combination of AD-like pathology induced by intracerebroventricular injections of the toxic 25 to 35 fragment of Aβ peptide (Aβ [25][26][27][28][29][30][31][32][33][34][35] ) and stroke (unilateral endothelin-1 injections in the striatum) in the rat also resulted in enhanced neuroinflammatory responses and AD-like pathology in the neocortex and hippocampus and were correlated with memory deficits detected using the Barnes circular platform test.…”
Section: September 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…Barba et al (2000) commented that the frequency of post stroke dementia depends on various factors such as the exclusion of hemorrhage or recurrent stroke, age range, length of follow-up, and diagnostic criteria. Srikanth et al (2006) in the first prospective data on long-term cognitive transitions in a population-based first-ever stroke cohort, found that stroke recurrence was associated with an increased rate of long-term global cognitive decline after a first-ever stroke; stroke recurrence, early poststroke cognitive impairment, and increasing age were independently associated with diagnosis of new clinical dementia two years after a first-ever stroke.…”
Section: Strokementioning
confidence: 99%
“…Другие авторы приводят похо-жие данные и отмечают, что те или иные КН имеются у 35-83% пациентов, перенесших инсульт [12,13], а у 6-32% из них они достигают степени деменции [13,14]. Повтор-ный инсульт существенно усугубляет когнитивный дефицит [15]. В популяционных исследованиях доля пациентов с де-менцией среди общего числа лиц, перенесших инсульт, соста-вляла 7%, через 3 года после инсульта -10%, через 25 лет -48% [5,16,17].…”
Section: о б з о р ыunclassified